Staying The Course: A Systematic Literature Review On Mooc Learners - Lisana, Lisana; Susanto, Alvin Fernando (Syntax Corporation, 2025)
Massive Open Online Courses have transformed access to education by offering flexible, learning opportunities. However, while initial adoption is widespread, sustaining learner engagement remains a critical challenge, marked by persistently low completion rates. This study addresses the growing academic concern around MOOC continuance intention, especially why learners choose to continue or discontinue participation. The purpose of this systematic literature review is to synthesize empirical research on MOOC continuance intention using the PRISMA framework. A total of 41 empirical articles indexed in Scopus, Web of Science, and Semantic Scholar were reviewed. This study answers four key research questions: What methods and measurements are commonly used? Which theoretical frameworks used? Which countries conducting studies? What key factors influence continuance intention? Findings reveal that quantitative methods using survey data are most prevalent, alongside studies using online reviews and mixed-method approaches. The Expectation-Confirmation Model emerges as the most frequently applied theoretical framework. China leads in publication volume, reflecting national policy support for MOOCs. Key influencing factors identified include perceived usefulness, satisfaction, perceived ease of use, confirmation, attitude, system quality, and perceived reputation. This review consolidates fragmented findings, builds a cohesive knowledge base, and offers practical insights for designing more effective, engaging, and sustainable MOOCs.